The menopausal subject at work: gendered embodiment and neoliberal management in the UK. - Rottenberg, Catherine; Gilchrist, Kate (Journal of Gender Studies, 2026)
In this paper, we examine five key UK policy documents that aim, inter alia, to address the concerns of ageing women in the workplace at a time when an estimated 900,000 women in the UK have left their jobs due to symptoms associated with menopause. Our analysis reveals that menopause has become a key site through which the contemporary struggle over how we (should) perceive gendered embodiment is being played out. This is evident in how these documents expand the menopausal subject: from exclusively cisgendered women to include trans, intersex and genderqueer people. Examining two key tensions that emerge—the invocation of menopause as natural and biological alongside a more inclusive menopausal subject, and the perceived naturalness of menopause alongside the construal of menopausal symptoms as abnormal , we maintain that expanding the menopausal subject is linked to a neoliberal managerial desire to address the challenges of all employees who experience menopause. Our findings thus point to a striking conjuncture between feminist and LGBTQI+ struggles to debunk binary understandings of sex and gender and the neoliberal State's desire to keep all older people experiencing menopause in the workforce, contributing to our understanding of the increase in menopause talk.